Methanol extract of Iraqi Kurdistan Region Daphne mucronata as a potent source of antioxidant, antimicrobial, and anticancer agents for the synthesis of novel and bioactive polyvinylpyrrolidone nanofibers - Muzammil, Khursheed; Kzar, Mazin Hadi; Mohammed, Faraj; Mohammed, Zahraa Ibrahim; Hamood, Sarah A.; Hussein, Talib Kh.; Hanoon, Saheb Jubeir; Qasim, Maytham T.; Hussien Alawadi, Ahmed; Alsalamy, Ali (Frontiers in Chemistry, 2023)
In this study, aqueous, ethanol, methanol, and hexane extracts from Iraqi Kurdistan Region Daphne mucronata were prepared due to the numerous applications and development of nanofibers in biological and medical fields, including food packaging, enzyme stabilization, and wound dressing. In the initial evaluation of the extracts, the antioxidant properties against DPPH, antimicrobial properties against 3-gram-positive bacterial species, 3-gram negative bacterial species, 3-common bacterial species between aquatic and human, and 3-fungal species, and anticancer properties against breast cancer cells were performed. The results proved that the methanol extract has the highest antimicrobial, antifungal, antioxidant, and anticancer properties. After identifying the compounds of prepared methanol extract using GC/MS, polyvinylpyrrolidone nanofibers containing methanol extract of Daphne mucronata were prepared. The structure and characteristics of prepared nanofibers were confirmed and determined using FTIR, TGA, BET, SEM, flexural strength, compressive strength, and hydrophilicity. Synthesized polyvinylpyrrolidone nanofibers containing methanol extract of D. mucronata were subjected to antimicrobial properties on the strains studied in methanol extract of D. mucronata. The antimicrobial properties of synthesized polyvinylpyrrolidone nanofibers containing methanol extract of D. mucronata were compared. The results showed that synthesized polyvinylpyrrolidone nanofibers containing methanol extract of D. mucronata have the potential to introduction bioactive natural synthesis nanoparticles.